Tragedy and Jubilee. Issue 3 (19th February 2016) - Toscano, Alberto
ABSTRACT: David Roediger's Seizing Freedom revisits the Civil War and Reconstruction from the standpoint of the emancipatory agency of slaves and their impact upon and ties with simultaneous movements against oppression. This commentary on the book explores the significance of what Roediger terms the 'tragedy of failed solidarities' to the story told in Seizing Freedom, putting it in the context of the development of a tragic conception of emancipation in the Marxist and Black Radical traditions, analysing its theoretical components, and drawing out its contribution to contemporary emancipatory thought.